2020
DOI: 10.52547/jccs.1.4.159
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aspirin on Pre-eclampsia and Fetal Growth Restriction in Obese Pregnant Women: A Randomized Controlled Clinical Trial

Abstract: Comparing pregnancy, childbirth, and neonatal ... [25] Williams ... [26] ECPPA: randomised trial of low dose aspirin ... [27] Acetylsalicylic acid for the prevention of preeclampsia ... [28] OC08.05: Impact of 1st trimester aspirin on population ... [29] Low dose acetylsalicylic acid in prevention of ... [30] Influence of maternal obesity on fetal growth at different ... [31] Prevention of preeclampsia and intrauterine growth ... [32] A prospective management study of slow-release ... [33] Evaluation of the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…A study by Abdi et al declared that the use of aspirin reduced the incidence of complications such as IUGR (20). Vanda et al showed that the use of aspirin (80 mg) reduced maternal and fetal complications in PE mothers (21). The present study also suggested that increasing aspirin dosage would prevent complications such as IUGR and IUFD.…”
Section: Discussionsupporting
confidence: 63%
“…A study by Abdi et al declared that the use of aspirin reduced the incidence of complications such as IUGR (20). Vanda et al showed that the use of aspirin (80 mg) reduced maternal and fetal complications in PE mothers (21). The present study also suggested that increasing aspirin dosage would prevent complications such as IUGR and IUFD.…”
Section: Discussionsupporting
confidence: 63%